Liquid crystalline polymers: Discovery, development, and the future. (12th August 2020) - Lyu, Xiaolin; Xiao, Anqi; Shi, Dong; Li, Yujie; Shen, Zhihao; Chen, Er-Qiang; Zheng, Shijun; Fan, Xing-He; Zhou, Qi-Feng
Abstract: Liquid crystalline polymers (LCPs) have drawn much interest because of their superior properties and widespread applications in high-performance polymer fibers, optics, energy storage, shape memory, surface modification, data storage, actuator, etc . LCPs can self-assemble into various liquid crystalline (LC) phases, such as nematic, smectic, columnar, and cholesteric phases. The self-assembling structures of LCPs can be influenced by architectures and chemical structures of the polymer backbone, mesogenic unit, flexible spacer, surrounding alkyl tail, etc . In the last decades, the structure-property relationships of LCPs have been researched extensively. In this perspective, the history, self-assembly, and applications of main-chain, side-chain, mesogen-jacketed, dendronized, main-chain/side-chain, and crosslinked LCPs are briefly reviewed. Finally, the future direction of research on LCPs is also discussed. Graphical abstract: Image 1 Highlights: The widespread use of liquid crystalline polymers has attracted much attention. Main-chain liquid crystalline polymers possess excellent mechanical properties. Side-chain liquid crystalline polymers are excellent functional and responsive materials. Liquid crystalline elastomers have huge potentials in actuator applications.